2013
DOI: 10.1177/0146167213481387
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Facial Emotion Judgment in Context

Abstract: Past research showed that East Asians' belief in holism was expressed as their tendencies to include background facial emotions into the evaluation of target faces more than North Americans. However, this pattern can be interpreted as North Americans' tendency to downplay background facial emotions due to their conceptualization of facial emotion as volitional expression of internal states. Examining this alternative explanation, we investigated whether different types of contextual information produce varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
5
35
0
Order By: Relevance
“…Their photographs were taken in standard experimental settings and did not include contextual cues such as location information and being alone. Since contextual cues can influence perception of personality and emotion (Ito, Masuda, & Hioki, 2012;Ito, Masuda, & Li, 2013), it is important to investigate how these cues in selfies are related to personality judgment.…”
Section: Zero-acquaintance Personality Judgmentmentioning
confidence: 99%
“…Their photographs were taken in standard experimental settings and did not include contextual cues such as location information and being alone. Since contextual cues can influence perception of personality and emotion (Ito, Masuda, & Hioki, 2012;Ito, Masuda, & Li, 2013), it is important to investigate how these cues in selfies are related to personality judgment.…”
Section: Zero-acquaintance Personality Judgmentmentioning
confidence: 99%
“…In fact, many cross‐cultural studies suggest that cultural variation is sensitive to situational constraints (e.g. Ito, Masuda & Hioki, ; Ito, Masuda & Li, ; Li, Masuda & Russell, ; Masuda & Kitayama, ; Norenzayan, Choi & Nisbett, ; Senzaki et al ., ). With this in mind, we chose to investigate how time constraints affect cultural variations in online decision‐making processes.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we chose to investigate how time constraints affect cultural variations in online decision‐making processes. Time pressure seemed particularly relevant as previous research by Ito and colleagues suggested that time constraints affect judgements of emotion in facial lineups (Ito et al ., , ), with non‐timed constrained judgements showing cultural differences and time constrained judgements showing cultural similarities. They argued that time constraints take away opportunities for participants to categorize images in culturally specific ways.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is still unclear whether ADI could take advantage of information provided by the contextual scene in which the emotion occurs (background, environment, posture), which is frequently present in real‐life situations and is known to impact the processing of emotional mental states. Specifically, congruent body posture, prosody, priming sentences, and background images are known to speed up and improve the processing of emotional facial expressions (e.g., Aviezer et al., ; De Gelder and Vroomen, ; Diéguez‐Risco et al., ; Ito et al., ). Therefore, because preliminary studies indicated that ADI are impaired in identifying emotional body postures (e.g., Maurage et al., ) and do not take advantage of congruent prosody when decoding emotional facial expressions (e.g., impaired cross‐modal integration) (Maurage et al., ,b; Valmas et al., ), we sought to examine whether ADI have lower performances than control individuals (CI) in decoding the emotional states of individuals displayed in contextual scenes (e.g., facial expression of a person being threatened).…”
mentioning
confidence: 99%